Examination of heart rate, rectal temperature, and salivary cortisol levels in calves within the first two hours post-birth - Terézia Hegerová; Peter Juhás; Cyril Hrnčár (Journal of Central European Agriculture, 2025)
This study, conducted at SPU's agricultural research centre in Nitra, aimed to monitor vital signs in newborn calves, specifically focusing on heart rate, rectal temperature, and salivary cortisol levels. The research observed no significant gender differences in the measured criteria. Heart rate showed noticeable variability, influenced by external factors. The examined calves exhibited an average heart rate of 165.64 ± 17.61 bpm, rectal temperature of 38.80 ± 0.74 °C, and salivary cortisol levels of 2.52 ± 1.34 ng/ml. Rectal temperatures in calves showed a decreasing trend after calving. A negative correlation was found between heart rate and rectal temperature. Analysis of salivary cortisol levels revealed a trend of decreasing cortisol with increasing birth difficulty. Additionally, a positive correlation was observed between heart rate and salivary cortisol. This study underscores the importance of monitoring calf vital signs for health assessment and growth prediction.